2015
DOI: 10.7287/peerj.preprints.1111v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigating readiness to use Internet and mobile services of diabetic patients of a middle-income country

Abstract: Background: Diabetes mellitus is increasing worldwide, especially in developing countries, as a consequence of urbanization. The use of the Internet and mobile service are increasing as well. The independent use of the Internet and mobile technologies by the patients could be a key step towards self-care management of the disease. Methods:A validated questionnaire with two parts was used and was completed by patients who came to two diabetic clinics for routine checkup. The first part consisted of 16 items col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…It was observed that younger patients exhibited a heightened interest and a stronger intention to utilize WBT in the future. Moreover, individuals with higher educational levels demonstrated a more favorable attitude towards the use of WBT, corroborating the findings of Song et al [41] and Jafari et al [42], which suggest that higher education is linked with increased confidence and better judgment in employing mHealth technologies. In addition, married participants demonstrated a greater interest in utilizing WBT for diabetes management.…”
Section: Discussionsupporting
confidence: 86%
“…It was observed that younger patients exhibited a heightened interest and a stronger intention to utilize WBT in the future. Moreover, individuals with higher educational levels demonstrated a more favorable attitude towards the use of WBT, corroborating the findings of Song et al [41] and Jafari et al [42], which suggest that higher education is linked with increased confidence and better judgment in employing mHealth technologies. In addition, married participants demonstrated a greater interest in utilizing WBT for diabetes management.…”
Section: Discussionsupporting
confidence: 86%
“…These results agree with those obtained in studies by Song et al [41] in the USA (2013) on pregnant women, and Jafari et al [31] in Iran (2015) in patients with T2DM. A review study showed that most pregnant women with higher education considered using the Internet useful and reliable [42].…”
Section: Principal Findingssupporting
confidence: 93%
“…To our knowledge, there is limited evidence on the use of mHealth applications and the attitude of patients with T2DM on their use in developing countries. In Iran, Jafari et al (2015) only studied Internet access and Internet-related issues of patients with T2DM, and reported that patients had poor level of the Internet use and the Internet was not the main diabetes-related information source [31].…”
Section: Introductionmentioning
confidence: 99%
“…However, 55% of the respondents still preferred to obtain health-related information from television, radio and educational films. 21 Both technology use 19 and the incidence of diabetes 6 have been increasing in Iran. It has become of national and general interest to bring forward research on internet-enabled patient education to determine future self-care management patterns of T2D.…”
Section: Patient Educationmentioning
confidence: 99%